Watermills and traditional landscape in the hills of the Algarve, Portugal - Barão, Marco (2014)
This paper focuses on the characterisation of a set of structures built on a portion of the Low Algarve landscape, creating a model of organization of different agricultural uses from the [re] construction of a water line fed by a spring of abundant waters. Combining the survey and the design of the set with the literature research, the different constructions of the structure will be described, which correspond, among others, to tanks, “levadas”, and three mills organised in sequence. The research will be framed by the characterisation of the Barrocal’s landscape and the different types of mills in the region, concluding with a reflection on some of the themes that determine their conservation.